Medication errors: analysis of situations reported by nursing staff - Carvalho, Viviane Tosta; Cassiani, Silvia Helena De Bortoli (Medicina (Ribeirao Preto), 2000)
Medication errors are one indicator of the quality of the health care provided to hospitalized patients. The purpose of this study was to analyze the situations of errors in medications related by nursing staff. The study was developed at the interior of the state of São Paulo, Brazil. Data were collected through interviews with 7 nurses, 1 nursing technician and 23 nursing auxiliaries from the medical clinic of the mentioned hospital. The author adopted as the methodological reference adaptation of the critical incident technique. The analysis enabled the identification of fifty six (56) situations grouped into four categories: failure in the accomplishment of policies and procedures (25), failure in the system of medications distribution and preparation by the pharmacy (15), communication failure (10) and knowledge failure (06). Thus, a safe environment with availability of human and physical resources is necessary for the prevention of future medication errors, as well as investments to provide knowledge on medication administration to nursing professional, aiming at a nursing care with quality.